2002
DOI: 10.1152/ajpendo.00547.2001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal gradients in shear stimulate osteoblastic proliferation via ERK1/2 and retinoblastoma protein

Abstract: The effects of pulsatile flow (temporal gradients in fluid shear) on rat UMR106 cells and rat primary osteoblastic cells were studied. Pulsatile flow induced a 95% increase in S-phase UMR106 cells compared with static controls. In contrast, ramped steady flow stimulated only a 3% increase. Similar patterns of S-phase induction were also observed in rat primary osteoblastic cells. Pulsatile flow significantly increased relative UMR106 cell number by 37 and 62% at 1.5 and 24 h, respectively. Pulsatile flow also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 44 publications
6
62
0
1
Order By: Relevance
“…These kinases have been shown to be important in the proliferation, growth, differentiation in many cell types [19][20][21][22] including osteoblasts [23,24]. Activation of MAPK has been shown to be important in shear-induced increases in OPN [35] and COX-2 mRNA expression [7] and cell proliferation [26]. In the present study, we found that only ERK1/2 was activated by fluid shear, becoming phosphorylated within 5 minutes of the onset of flow with peak activation observed after 30 minutes.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These kinases have been shown to be important in the proliferation, growth, differentiation in many cell types [19][20][21][22] including osteoblasts [23,24]. Activation of MAPK has been shown to be important in shear-induced increases in OPN [35] and COX-2 mRNA expression [7] and cell proliferation [26]. In the present study, we found that only ERK1/2 was activated by fluid shear, becoming phosphorylated within 5 minutes of the onset of flow with peak activation observed after 30 minutes.…”
Section: Discussionsupporting
confidence: 54%
“…These members of the MAPK family have been implicated in the regulation of cellular growth, differentiation and apoptosis in numerous cell types [19][20][21][22] including osteoblasts [23,24]. Several studies have shown that ERK1/2 is activated by fluid shear in osteoblasts [7,25,26]. Studies have also shown that Ca 2+ i is important to ERK1/2 activation in osteoblasts [24,27], although it is unclear whether this Ca 2+ i -induced activation results from extracellular Ca 2+ entry or intracellular Ca 2+ release.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured human osteoblasts, ERK-1/2 blockade prevented shear-induced proliferation and matrix synthesis (43). Tenocytes appear to share elements of a load-sensing mechanism similar to osteoblasts and osteocytes; stretch-activated potassium and calcium channels, internal calcium release, interstitial ATP release, and gap junction signaling all play a role in the proliferative response to membrane deformation, substrate deformation, or fluid shear (43)(44)(45)(46)(47). In elongated tenocytes, proliferation and collagen synthesis in response to ex vivo loading of chicken flexor tendon could be blocked by a gap junction inhibitor (48).…”
Section: Discussionmentioning
confidence: 99%
“…This extracellular ATP accumulation may in turn trigger other P2 receptor signaling pathways and cause an increased osteogenic response possibly via ATP-dependent phosphorylation of ERK, (11,17) which then stimulates osteoblastic proliferation and drives the osteogenic response. (18) In conclusion, this study examined the role of P2Y 13 receptor in bone osteogenic response to mechanical loading in vivo and in vitro. Deletion of the P2Y 13 R leads to higher bone formation, mainly in cortical compartment, than WT upon mechanical loading in vivo, possibly because of the lack of P2Y 13 R regulated negative feedback pathway for ATP release.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%